(untitled) (European Journal of Education, 2023)
Learning Management Systems (LMS) or Learning Content Management Systems (LCMS) are the core of e-learning platforms and have evolved according to the development of new information and communication technologies. In this type of software there are many products on the market, some developed by the institutions themselves (in-house), others are free and open source software (FOSS) and others are more commercial, varying in functionality and technology, but almost always adhering to the standards used in e-learning so that learning objects fulfill their purpose of being usable and reusable. This paper introduces you to current LMS / LCMS, main functions, distinctive features, related standards, and their current status. Then there is a presentation of Machine Learning as a branch of Artificial Intelligence and Cognitive Computing as a fusion discipline between computation, cognition, psychology and artificial intelligence, to end in a proposal for the incorporation of these technologies in a new generation of e-learning platforms, all in an integrated framework of interoperability and governance.